2010
DOI: 10.1007/s10646-010-0473-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of abamectin to the terrestrial isopod Porcellio scaber (Isopoda, Crustacea)

Abstract: To determine effects of the antiparasitic veterinary drug abamectin on the isopod Porcellio scaber, animals were exposed for 21 days to Lufa 2.2 soil spiked at concentrations of 3-300 mg/kg dry soil. After exposure, abamectin residues in the isopods were analysed using a novel analytical method. Toxicity was evaluated on different levels of biological organisation: biochemical, cellular and the individual organism. Measurements included glutathione S-transferase (GST) activity and stability of cell membranes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Contradictory results have been reported concerning the effect of avermectins on GST levels in the literature. It was reported that avermectins increased GST activity in some mites and whitefly and did not change it in the Brazilian populations of tomato leaves . Similar studies have also been investigated in some animal tissues for carbonic anhydrase (CA) enzyme activity .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Contradictory results have been reported concerning the effect of avermectins on GST levels in the literature. It was reported that avermectins increased GST activity in some mites and whitefly and did not change it in the Brazilian populations of tomato leaves . Similar studies have also been investigated in some animal tissues for carbonic anhydrase (CA) enzyme activity .…”
Section: Discussionmentioning
confidence: 79%
“…Li et al reported that avermectins reduced SOD activity and increased POD and GST enzyme activity in vitro. Kolar et al expressed that abamectin did not induced GST activity in vivo, and GST had a minor role in the detoxification of abamectin. Contradictory results have been reported concerning the effect of avermectins on GST levels in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Several different endpoints have been proposed, but considering the difficulty of culturing Porcellio scaber in the laboratory survival, growth and food consumption rate so far have been used most frequently (see e.g. Odendaal and Reinecke 2004, Nolde et al 2006, Kolar et al 2010). Another interesting endpoint may be related to the composition of the gut microflora of isopods (Drobne et al 2002).…”
Section: Toxicity Testsmentioning
confidence: 99%
“…Porcellio scaber has been used for metal toxicity testing of various elements such as zinc , cadmium , and cobalt , considering different lethal and sublethal endpoints. In addition, the toxic effects of nanoparticles like titanium dioxide and different organic compounds have been investigated with P. scaber . However, a standardized test protocol is still lacking.…”
Section: Introductionmentioning
confidence: 99%